Book Reading Habits of College Level English Language Teachers - Tiwari, Hari Prasad (KMC Journal, 2022)
Reading only textbooks or coursebooks is not enough for English language teachers. In addition to textbooks, they should read several books for their academic advancement. Keeping this in mind, this descriptive survey design under quantitative research tried to find out the book reading habits of the college level English Language (EL) teachers. The participants of the study consisted of 20 English language teachers who have been teaching English in different Tribhuvan University (TU) affiliated colleges located in Banke district. The participants were selected employing simple random sampling technique. The data was collected using a questionnaire which included altogether fifteen questions. The first ten questions were closed ended and the last five questions were open ended. The collected data was analyzed based on the descriptive statistics technique of data analysis. The results of the study showed that the average number of books the college teachers read in a year is approximately four. Similarly, the majority of college teachers have no habits of reading even a single book in a month. Another finding of this study is that college teachers prefer extensive reading over intensive one. Moreover, the college teachers believed that the library is the main source for college teachers to read.